DESAIN NOISE BARRIER LIGHT RAIL TRANSIT (LRT) PALEMBANG UNTUK MENGURANGI TINGKAT KEBISINGAN - Joni Arliansyah; Edi Kadarsa; Rida Melania (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2022)
This study aims to determine the level of noise generated by the Palembang City LRT when passing and compared with applicable standards according to The Decree of the State Minister of the Environment No. 48/MENLH/11/1996 of the Republic of Indonesia and standard of World Health Organization (WHO). Then find out the map of exposure to noise effects around the Palembang LRT rail area and recommend an effective barrier design to reduce LRT noise. Data collection was conducted at 3 locations, namely 2 locations for the Palembang city LRT corner on Jl. Jend. Sudirman and Jl. Demang Lebar Daun and one straight location on Jo. A. Rivai. From the analysis, The highest noise level when the LRT passes is in a position in the corner of 91, 68327 dBA. All noise values obtained in the analysis of exposure maps at the farthest dix xstances still reached in the analysis also show high values. The analysis results showed that the barrier design found that the most recommended material for reducing the LRT noise level is polycarbonate material with a density of 14 kg/m2, a thickness of 12 mm, and a transmission loss value of 33 dBA. This material has a thin thickness, low density, and has a transmission loss value so that this material is thinner, lighter and can reduce noise greater than other materials, namely, with a noise value after reduction of 58,68327 dBa.